VOCABULARY MASTERY THROUGH PERFORMING OF KEY WORD BASED ON DICTIONARY - Upik Supriyati; Eryon Eryon; As Adannas; Rika Marlina; Resky Resky (SIGEH ELT : Journal of Literature and Linguistics, 2021)
Performing of key word based on dictionary technique is one of the way to influence the students’ vocabulary mastery, so the researcher can motivate the students in learning English by performing of key word based on dictionary technique. The English teacher is able to find many ways to enrich students’ vocabulary mastery. The students should be active and innovative when they are given the performing of key word based on dictionary technique, especially in learning of vocabulary. Performing of key word based on dictionary technique can make the students are enjoy. The students should be involved in learning English in their vocabulary mastery by  using performing of key word based on dictionary technique. Then, by using performing of key word based on dictionary in learning English, it helps the students influence and enrich their vocabulary mastery. It is better if the students learn vocabulary by using performing of key word based on dictionary since the students are more responsible, relax, and active.